Mediterranean immigration in the post-Arab Spring - Ferreira, Susana (2014)
This communication explores how the Arab democratic wave affect(ed) the migratory fluxes within the Mediterranean region and aims to deconstruct the common perception of “immigrant invasion” in Europe. The increased instability of the Mediterranean region has highlighted the migratory pressure and triggered two massive refugee crises in Southern Mediterranean, Libya and Syria. The political and social tensions of the Arab Spring have shaken these states economies and have changed migration patterns and challenged regional security. Nevertheless, the Arab Spring did not cause a massive influx of migration to Europe. On the contrary, the population affected looked for shelter mostly in neighbouring countries (South-South mobility). Focusing in the MENA countries, it is our aim to deconstruct these perceptions of large-scalefluxes regarding Mediterranean migrations and analyse how the securitisation process is changing the European border management.